ANALISIS PEMBERIAN INSENTIF DAN MOTIVASI TERHADAP KINERJA GURU PADA MTS NURUL HUDA KALANGANYAR SEDATI - Studiviani, Pramita; Hidayat, Rachmad (JEM17: Jurnal Ekonomi Manajemen, 2016)
The problems to be studied in this research is the relationship between a teacher's performance against incentives. The core of this study is focused on one of thefactors that affect the performance of a teacher that is an incentive. Based on the above,the purpose of this research is to know is there any incentive effect on the performanceand motivation of teachers at MTs Nurul Huda Sedati. The results using the F testknown that Incentive (X1), and motivation (X2) has positive influence on performance(Y), with a significance level of less than 0.05. Effect of incentives (X1), and motivation(X2) on the performance (Y) shows the positive direction, meaning that the higher theincentive (X1) and motivation (X2) is good, the higher performance of a given teacher.This incentive is a component that is worth more to the teachers at MTs Nurul HudaKalanganyar Sedati, they should each teacher must provide performance that isproportional as experts and motivate yourself and comrade in order to create arelationship of positive feedback between teacher one with teachers the others and thecreation of a good cooperation in education.Keywords: incentive, motivation and performance